Regulatory cytokines modulate early isotype-specific response associated with COVID-19 survival - Castro-Trujillo, Sebastián; Castro-Meneses, Juanita; Rojas, María Clemencia; Castro-Amaya, Marcela; Lastra, Giovani; Narváez, Carlos F. (Frontiers in Immunology, 2025)
Identifying immune markers driving early and effective antibody response in patients with severe coronavirus disease 2019 (COVID-19) is critical due to the threat of future coronavirus pandemics, incomplete global vaccination, and suboptimal booster coverage. Patients with life-threatening severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are characterized by dysregulated thromboinflammation and cytokine storm that could influence the isotype virus-specific antibody response and the subsequent clinical outcome. We investigated the association between COVID-19-related mortality with the dynamics, magnitude, and relative avidity of nucleoprotein (N), spike (S), and receptor-binding domain (RBD)-specific IgM, IgA, and IgG in circulation. We also assessed the relationship between the virus-specific antibody responses and cytokine patterns, as well as systemic and pulmonary thromboinflammation markers. This multicenter study included COVID-19 patients hospitalized early in the pandemic, classified as survivors (n=62) and non-survivors (n=17). We developed indirect enzyme-linked immunosorbent assays (ELISAs) to evaluate each virus-specific isotype using well-characterized outpatient COVID-19 (n=180) and pre-pandemic cohorts (n=111). The pro-inflammatory interleukin (IL)-6 and tumor necrosis factor (TNF)-α, as well as the regulatory IL-10, transforming growth factor (TGF)-β1, and soluble tumor necrosis factor receptor I (sTNFRI) levels were evaluated. The ELISAs performed highly for all virus-specific isotypes, although modest for IgM-N. Non-survivors increased N-specific, but no S-specific, IgM and IgA responses throughout the disease course and, more notably, a delayed class switching to IgG-S and IgG-RBD compared to survivors. No differences were observed in the virus-specific IgG relative avidity. Survivors exhibited an antibody response proportional to the degree of systemic and pulmonary thromboinflammation, whereas non-survivors showed those dissociated because of their uncontrolled severe thromboinflammation. Only the survivors showed a dominant regulatory cytokine pattern in the early phase of infection (<10 days after symptoms onset), which strongly correlated with developing IgG-S and IgG-RBD protective antibodies. We developed easy-to-use immune assays that enable patient monitoring and identify at-risk populations in low- to middle-income regions. Non-survivors displayed an ineffective N-mediated antibody response, marked by an inability to control inflammation and a compromised time-dependent class switching toward S and RBD-specific IgG. The regulatory cytokine axis, including TGF-β1, maybe a critical immune correlate of effective antibody-mediated immunity in COVID-19.